The michigan guide to English for academic succes and better toefl test scores Catherine Mazak, Lawrence J. Zwier, Stafford - Yulmaz - MAZAK, Catherine; Zwier, Lawrence J; Stafford Yulmaz, Lynn (The University of Michigan Press, 2005)
xvii, 298 hlm ilus 28 cm